Implications of the 'new rangeland paradigm' for natural resource management - Hiernaux, Pierre H.Y. (University of Copenhagen, 2000)
In the Sahel, opportunistic resource management operates with communal access rights and land tenure systems that include particular access rights and land tenure systems that include particular access rights to key pastoral resources. The pastoral Development approaches attached to the concept of opportunistic resource management privilage institutional Development and economic policies, and minimise technological Developments that had little success in the livestock agriculture Development projects of the 1970's. Reconcilation of ecological theory with social science and agricultural Development first requires a clarification of the theoritical bases of the new pastoral paradigm. This task is attempted in the first part of the paper. The implications of the paradigm elements for natural resource management, in general and livestock agriculture Development, in particular are discussed in the second part of the paper with special reference to the Sahel in west Africa. Topics of discussion include the new rangeland pardigm; implications for natural resource management. Under this first topics are outlined the state and transition model, the non equilibrium model the succession model, and ecological function of ecosystem heterogeneity. Unider the second topic are discussed sedentary livestock management and carrying capacity, livestock mobility and opportunistic pastoral resource management, local and regional livestock mobility, land tenure policies, and destocking restocking - livestock feed markets.